PENGARUH SOSIAL, EKONOMI, BUDAYA DAN AGAMA TERHADAP KEPUASAN MASYARAKAT PASCA REALISASI JEMBATAN SURAMADU - Amir, Azhar (JPAP: Jurnal Penelitian Administrasi Publik, 2015)
Suramadu bridge has been in operation for three years, but until now have not been ableto boost economic development and Madura. Precisely the community with therealization Suramadu they complained because he was broke by big capital. While theywere able to sell at huge profits claimed to be new business opportunities for theirlongest bridge. In fact, the bridge was deliberately created to generate economicopportunities of the Madurese. Formulation Research, a. Is the satisfaction of the peoplein the social, economic, cultural and religious jointly met after the realization of thelongest bridge? b. Is the satisfaction of the people in the social, economic, cultural andreligious partially fulfilled after the realization of the longest bridge? c. Among thesatisfaction of the people in the social, economic, cultural and religious, which is themost dominant post-realization Suramadu? This study uses quantitative methods.Results of testing the coefficient of determination R2 = .835 (83.5%), meaning that allof these variables together can explain the variation of the dependent variable aroundthe longest Public Satisfaction in Bangkalan (Y), amounting to 83.5%. Fourindependent variables have a strong relationship with the dependent variable, this isindicated by the R value of .914a approaches 1. The result showed that the variables ofSocial Aspects (X1) has a beta coefficient of a high standard is .415 and larger than thethree independent variables the other with a contribution of 41.5% to the influence ofCommunity Satisfaction approximately longest in Bangkalan (Y).Keywords: Social, Economic, Cultural Religious Community Satisfaction, Suramadu